Group Counseling with the Motivational Interviewing Technique to Alleviate Students' Mild Depression Symptoms - Barutu, Anisa Fitria; Damayanti, Rika; Thahir, Andi (Sinergi International Journal of Psychology, 2023)
Depression is a common phenomenon in Indonesia, particularly among adolescents. Many teenagers today suffer from mild to severe depression as a result of stress from both internal and external factors, which can lead to mental problems and even suicidal thoughts. This fact can be seen from the results of the pretest conducted on students in class 11 Mathematics and Natural Sciences  3, which resulted in eight students who have mild depression categories. Therefore, an effort should be made to reduce the level of depression symptoms by providing group counseling using motivational interviewing techniques so that the level of depression symptoms does not rise to the severe depression level. This study aims to see how effective group counseling with the motivational interviewing technique is in helping class 11 Mathematics and Natural Science 3 of State Islamic High School 2 Bandar Lampung students overcome mild symptoms of depression. This study employed a pre-experimental research method with a one-group pretest-posttest design. The data-collecting techniques employed were questionnaires, interviews, observations, and documentation. The purposive sampling technique was utilized to select eight students as the sample from class 11 Mathematics and Natural Sciences 3. The treatment consisted of six meetings, including pretests and posttests. The results revealed a pretest score of 263 with an average of 32.8 and a posttest score of 151 with an average of 18.8. There is a noticeable difference after receiving group counseling with motivational interviewing technique. The results of the T-test and N-gain indicated a decrease in the level of depression experienced by students, as seen by the pretest and posttest scores.